Designing for social interaction in high-density housing: A multiple case analysis of recently completed design-led developments in London - Mellen, Hal; Short, Michael (Frontiers in Sustainable Cities, 2023)
Over the past two decades, the Greater London Authority (GLA) has pursued the delivery of high-density development in London in order to respond to population growth whilst protecting the green belt. Though high-density places have been associated with sustainable outcomes, it is well documented that residents interact less frequently and build fewer relationships in these environments. This can be particularly detrimental since social contact is fundamental for our general wellbeing and happiness. In response to this problematic, this study explored if and how we can design for social interaction in high-density housing. To do so, it adopted the process of inducting theory from case studies. Firstly, three case studies of recently completed developments were undertaken to determine whether social interaction was a driving factor in the design process, the type and location of social interactions, and clarify the influence of physical design on social contact in comparison to other factors. Three research methods were used to find answers to these questions including interviews with the residents and architects of the schemes, participant observation, and content analysis. These design-led schemes were chosen for investigation as award-winning developments which had received commendation for creating the foundations for a strong community. Next, a cross-case comparison was undertaken to identify hypotheses that addressed the research question and objectives. Providing support for existing literature in the context of high-density housing, it was discovered that limiting the number of apartments to a building allows for collective stewardship, and that communal areas shared by smaller groups are used more intensively. Moreover, combining shared paths and communal areas was observed to support fleeting interactions and helped to nurture a local sense of community. New findings included that externalizing the circulation spaces of multi-story apartment blocks can facilitate conversations between neighbors, and that bike stores can represent an epicenter for contact if internalized and co-located with shared paths. Notably, the impact of physical design factors was not deterministic.